ARCHITECTURAL AND DESIGN ISSUES ENSURING SAFE EVACUATION FROM BUILDINGS IN EMERGENCY SITUATIONS: A CASE-STUDY RESEARCH - Uktam, Nazarov; Muhammadnodir, Kamolov (Research Focus International Scientific Journal, 2026)
This article examines architectural and design issues aimed at ensuring safe evacuation from public buildings in emergency situations. The study is based on the results of three empirical case studies conducted by A. Sagun, C. J. Anumba, and D. Bouchlaghem, as well as an analysis of foreign scientific sources published on the topic. The article discusses the impact of building geometry, capacity, circulation routes, compartmentalization, exit-choice behavior, alarm systems, and orientation systems on safety. The results are summarized as practical recommendations for architectural practice in Uzbekistan.